Diet, Pregnancy Distance, and Age at Marriage with Chronic Energy Deficiency (KEK) in Pregnant Women - Petrus Petrus; Rofiqoh Rofiqoh; Anisa Fadila (Jurnal Health Sains, 2023)
Kronic energy deficiency (kekurangan energy kronis/KEK) is condition someone that suffer food shortage regularly (Chronic) marked humerus (LILA) <23,5 cm with the result that appearing health problems. Prevalence of chronic energy deficiency (KEK) in expectant mother at year 2013 nationally is 24,2% and decrease be 17,3% at years 2018 based Riskesda data 2018. This research have urpose to know   relationship nourishment system, Spacing pregnancy, and marriageable age toward chronic energy deficiency (KEK) at Puskesmas Tongauna Utara occupation area in years 2021. This research as analistical observation research by approach “Cross Sectional Study” And have conducted in date 29 March-03 at Puskesmas Tongauna Utara occupation area. Sample in the research is 49 expectant mother. This research   using “total sampling technique” is technique taking sample same with population. Then, this research using “Pearson Correlation” statistics test. The result of this research show that expectant mother which have goodn ourishment system is 51,0%, then have not nourishment system enough is 49,0%, expectant mother that have spacing high risk pregnancy is 16,3% then, that have not risk to pregnancy is 83,7%. The expectant mother have risk to marriageable age is 12,2% then, the expectant mother have not risk to marriageable age is 87,8%. The result of try out using spearmen correlation show that there is not relationship nourishment system toward expectant mother KEK (P = 0,376), spacing pregnancy toward expectant mother KEK (P = 0,4420), marriageable age toward expectant mother KEK (P = 0,165).